Peningkatan Keterampilan dan Teknik Presentasi bagi Pustakawan Perguruan Tinggi - Kurniasih, Nuning (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
The purpose of this study is to improve the skills and presentation techniques for librarians and library managers at Padjadjaran University. The dedication uses study analysis method. The results showed that there was an increase in presentation skills and techniques for librarians and library managers at Padjadjaran University through workshops. Workshop participants attended all the series of activities, starting from listening to the presentation of the material by the speakers, discussing it, and doing the practice of making presentation material using Prezi software. It is expected that will come. Participants will further develop with these activities.